Under siege : P.L.O. decisionmaking during the 1982 war - Khalidi, Rashid (Columbia University Press, 1986)
A fascinating and often terrifying firsthand account of the 1982 war in Lebanon, Under Siege vividly reveals the complex negotiations and military maneuvers which ended with the evacuation of the P.L.O. from Beirut. Rashid Khalidi, a Palestinian, lived with his family in Beirut during the siege and ensuing massacres. Using many usually inaccessible sources, such as P.L.O. telexes and government messages, and interviews with key military officials and diplomats, he tells the story from the compelling viewpoint of those living amid the fighting. Khalidi provides a carefully detailed picture.
Keywords: Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah.; Munaẓẓamat at-Taḥrīr al-Filasṭīniyyah.; Munaẓẓamat al-Taḥrīr al-Filasṭīnīyah; Lebanon -- History -- Israeli intervention, 1982-1985.; Palestinian Arabs -- Lebanon -- Politics and government.; Palestiniens -- Liban -- Politique et gouvernement.; Liban -- Histoire -- 1982-1985 (Invasion israélienne); HISTORY -- Middle East -- General.; HISTORY -- Middle East -- Israel.; Palestinian Arabs -- Politics and government; Lebanon; 1982-1985; History